Customer Segmentation Using RFM Model - Hendrawan, Made Chandra; Hendra Suputra, I Putu Gede (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2020)
At the time of the ASEAN Economic Community (MEA), Indonesia was selected by several companies from other countries to sell its products, including overseas paint companies. Therefore, the increasingly fierce market competition business is unlikely to focus solely on products sold, but it is also important to pay attention to the process of managing customer relationships with retailers. Segmentation is an early process that knows which customers can be sustained. In segmentation, customers who have certain similarities will be grouped into one. Customer segmentation is a model built in grouping customers according to certain standards to be used as a variable grouping. Customers will be the same group if they have certain similarities, while different groups or segments are customers who have different characteristics.